PELATIHAN PUBLIC SPEAKING BAHASA INGGRIS TEKNIK USING NOTE SANTRI HIDAYATUL FAIZIEN GARUT - Farida Farida; Heri Hendrawan (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Modernization of the times does not only require the development of critical and creative thinking skills, being a public speaker needs to be habituated in daily life, especially for students as a life skill. This author identifies the effectiveness of English public speaking using the note-taking technique as a potential that makes students capable of becoming good and confident public speakers. Purpose of this community service is to help improve public speaking skills through a structured and comprehensive approach using the first method of presenting material about the importance of public speaking and 2nd material about English that needs to be learned by students, the second is practicing students understanding of the material and evaluations carried out every day when the training takes place and a week of observation after the training. This training is shown by getting a very positive response from students and high enthusiasm, in addition to increasing self-confidence and successful techniques that are significantly shown when the muhadhroh. The effectiveness of student training in participating in community service is that 95,24% of participants are identified as giving confident responses.